CLINICAL PRACTICE AND SPIRITUALITY - Rivera Ledesma, Armando; Montero López Lena, María (Anales de Psicología / Annals of Psychology, 2007)
Who must be in charge of the spiritual necessities of patients, and how? The literature reports evidence about the importance of the association between the spiritual life and the physical and mental health in people (e.g. Meisenhelder y Chandler, 2002; Silberfarb, Anderson, y Rundle, 1991; Koenig, George y Siegler, 1988). Attend the spiritual neces-sities of the patients in medical care is a daily clinical reality (Mueller, Plevak, y Rummans, 2001), in traumatology, oncology, and all those areas where the patient is confronted with his own death, or the death of loved beings, and the World Health Organization had emphasized his importance (Dein y Stygall, 1997). However, nowadays, there are efforts to determine how this function has to be done, and how must operate each clinic (Kristeller, Zumbrun y Schilling et al.,1999; Daaleman y VandeCreek, 2000). The present paper analyzes this problem, exploring how to insert the spiritual world inside the four basic resources in psychotherapy that constitutes the clinical arsenal in psychology: accompanying, counseling, psychotherapy, and psychotherapeutic systems.